Property prices, housing policies for collateral and resale constraints. Issue 2 (3rd April 2017) - Hui, Eddie C. M.; Zhong, Jiawei; Yu, Kahung
ABSTRACT: The question of whether significant impacts of Loan-to-value (LTV) ratio and Special Stamp Duty (SSD) on residential property market prices exist has been hotly debated. This study aims to investigate the long-term and short-term impacts of LTV ratio and SSD on property prices in Hong Kong. In the study period, the interest rate is low, and the growth rate of housing mortgage is slower than the growth rate of market prices. The findings indicate that changes in LTV ratio cannot change the potential purchasers' willingness to purchase housing flats over the past ten years. SSD, on the other hand, only have a more prominent long-term impact on larger properties (more than 70 m 2 ) by directly reducing the transaction volumes, compared with that on smaller (less than 70 m 2 ) ones.